Accurate Measurement of First Metatarsophalangeal Range of Motion in Patients with Hallux Rigidus. Issue 1 (19th August 2016) - Vulcano, Ettore; Tracey, Joseph A.; Myerson, Mark S.
Category: Midfoot/Forefoot Introduction/Purpose: The reliability of range of motion (ROM) measurements has not been established for the hallux metatarsophalangeal (MTP) joint in patients with hallux rigidus. The aim of the present study was to prospectively assess the clinical versus radiographic difference in ROM of the arthritic hallux MTP joint. Methods: One-hundred consecutive patients who presented with any grade of hallux rigidus were included in this prospective study to determine the hallux MTP dorsiflexion. Clinical range of motion using a goniometer and radiographic range of motion on dynamic xrays was recorded. Inter and intra-rater reliability were calculated. Results: The mean difference between clinical and radiographic dorsiflexion was 13°. This difference was statistically significant. For all measurements clinical dorsiflexion was equal or less than radiographically-measured dorsiflexion. The difference was significantly greater in patients with a clinical dorsiflexion of less than 30° than in patients with 30° or more. Radiographic measurement of hallux dorsiflexion had an excellent intra- and inter-observer reliability. Conclusion: This study describes a reliable, reproducible, and straightforward method of measuring hallux MTP ROM that eliminates the "human" component of measuring clinical ROM and all the variables that are encountered when making said measurement.